Pengaruh Pertumbuhan Ekonomi dan Pengeluaran Pemerintah Terhadap Angka Kemiskinan di Kabupaten Tabalong - Nurul Izzati (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2018)
Poverty is a multidimensional problem that is stillfaced by Tabalong Regency. Poverty alleviation is continuously to beintegrated comprehensively and its involving various aspects of the community life. One of the efforts by the government of Tabalong Regency to reduce poverty is using various policies and programs that supported by all stakeholders.In 2016 and 2017, the poverty rate was reduced that were probably due to the positive impacts of government programs and policies on economic development that can be seen from two variables such as economic growth and government expenditure. This study aims to find out the influence of economic growth and government expenditure on poverty in Tabalong Regency. This study uses the explanatory research with the quantitative method. This study uses secondary data of economic growth and government expenditure in fifteen years and analyzed by using a regression analysis. The results of this study proved that the government expenditure has an effect on the poverty rate, while the economic growth does not affect the poverty rate in Tabalong Regency. The output of this research can be used as arecommendation for the policy makers in relation with the poverty alleviation. abstrak Kemiskinan merupakan permasalahan multidimensi yang masih diha dapi Kabupaten Tabalong. Pengentasan kemiskinan terus dilakukan secara komprehensif dan terpadu, melibatkan berbagai aspek kehidupan masyarakat. Salah satu upaya Pemerintah Kabupaten Tabalong untuk menurunkan angka kemiskinan adalah melalui berbagai kebijakan dan program yang didukung oleh semua stakeholder Penelitian ini bertujuan untuk mengetahui pengaruh pertumbuhan ekonomi dan pengeluaran pemerintah terhadap angka kemiskinan di Kabupaten Tabalong.Penelitian ini merupakan penelitian eksplanato ri dengan menggunakan pendekatan kuantitatif. Data yang digunakan adalah data sekunder pertumbuhan ekonomi, pengeluaran pemerintah danangkan kemiskinan selama lima belas tahun dan dianalisis dengan regresi.Hasil penelitian ini membuktikan bahwa pengeluaran pemerintah berpengaruh terhadap angka kemiskinan, sedangkan pertumbuhanekonomi tidak berpengaruh terhadap angka kemiskinan di Kabupaten Tabalong.Hasil penelitian ini diharapkan dapat menjadi bahan pertimbangan bagi pengambil kebijakan terkait penanggulangan kemiskinan.